Predictors of long-term smoking cessation: results from the global adult tobacco survey in Poland (2009-2010) - Kaleta Dorota; Korytkowski Przemysław; Makowiec-Dąbrowska Teresa; Usidame Bukola; Bąk-Romaniszyn Leokadia; Fronczak Adam (BMC, 2012)
Abstract Background Expanding the information on determinants of smoking cessation is crucial for developing and implementing more effective tobacco control measures at the national as well as European levels. Data on smoking cessation and its social correlates among adults from middle-income countries of Central and Eastern Europe are still poorly reported in the literature. The aim of the study was to analyze the association of socio-demographic indicators with long term tobacco smoking cessation (quit smoking for at least one year prior to interview) among adults. Moreover, we evaluated motives for giving up smoking from former smokers. Methods Data on former as well as current smokers' socio-demographic and smoking-related characteristics were derived from the Global Adult Tobacco Survey (GATS). GATS is a cross-sectional, nationally representative household survey implemented in Poland between 2009 and 2010. GATS collected data on a representative sample of 7,840 individuals including 1,206 individuals who met the criteria of long-term smoking cessation and 2,233 current smokers. Smoking cessation rate was calculated as the number of former smokers divided by the number of ever smokers. Logistic regression analyses were used to obtain odds ratios (ORs) and 95% confidence interval (CI) of the broad number of variables on successful cessation of smoking. Results Among females the quit rate was 30.4% compared to 37.9% in males (p < 0.01). Former smokers declared concerns about the health hazard of smoking (60.8%) and the high price of cigarettes (11.6%) as primary reasons for smoking cessation. Older age, high education attainment, awareness of smoking health consequences was associated with long-term quitting among both genders. Also employed males had over twice the probability of giving up smoking compared with unemployed, and being religious did not contribute to successful smoking cessation. Conclusion Results indicated that smoking cessation policies focused on younger age groups are vital for curbing tobacco epidemic in Poland and should become a public health main concern. There is also the need for interventions to raise awareness on smoking health risks and quitting benefits are crucial to increase cessation potential among adult smokers. Nevertheless further effort needs to be done to prevent smoking uptake.